IL-17A-producing NKp44(−) group 3 innate lymphoid cells accumulate in Familial Adenomatous Polyposis duodenal tissue - Kim M. Kaiser; Jan Raabe; Michael ToVinh; Gudrun Hack; Sarah Ahmad; Niko Müller; Julia Cassella; Sofia I. Walravens; Paula Alfaro; Lauren Arias Garcia; Dominik J. Kaczmarek; Tim Marwitz; et al. (Nature Communications)
Abstract Familial adenomatous polyposis (FAP) is an inherited gastrointestinal syndrome associated with duodenal adenoma formation. Even among carriers of the same genetic variant, duodenal phenotypes vary, indicating that additional factors, such as the local immune system, play a role. We observe an increase in duodenal IL-17A(+)NKp44(−) innate lymphoid type 3 cell (ILC3) in FAP, localized near the epithelium and enriched in adenomas and carcinomas. Elevated IL1B, IL23A, and DLL4 transcript levels correlate with IL-17A(+)NKp44(−)ILC3 accumulation, and in vitro studies with duodenal organoids confirmed this relationship. Bulk RNA sequencing reveals upregulated Reactive oxygen species (ROS)-inducing enzymes DUOX2 and DUOXA2 in FAP adenomas. IL-17A-stimulated FAP organoids show increased DUOX2/DUOXA2 expression, Duox2 protein, and ROS production, leading to DNA damage, suggesting a mechanism by which these immune cells promote tumorigenesis. These findings suggest IL-17A(+)NKp44(–)ILC3s may contribute to a local environment that makes the epithelium more submissive for oncogenic transformation in FAP.